2020
DOI: 10.1126/sciadv.aaz2441
|View full text |Cite
|
Sign up to set email alerts
|

Schizorhodopsins: A family of rhodopsins from Asgard archaea that function as light-driven inward H + pumps

Abstract: Schizorhodopsins (SzRs), a rhodopsin family first identified in Asgard archaea, the archaeal group closest to eukaryotes, are present at a phylogenetically intermediate position between typical microbial rhodopsins and heliorhodopsins. However, the biological function and molecular properties of SzRs have not been reported. Here, SzRs from Asgardarchaeota and from a yet unknown microorganism are expressed in Escherichia coli and mammalian cells, and ion transport assays and patch clamp analyses are used to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
124
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(133 citation statements)
references
References 46 publications
9
124
0
Order By: Relevance
“…The alkalization was largely eliminated by the addition of a protonophore, 10 μM CCCP (carbonyl cyanide m-chlorophenylhydrazone), suggesting that SzR4 functions as an inward H + pump as reported previously 13 . The purified SzR4 showed a maximum absorption wavelength (λmax) at 557 nm, identical to that of SzR1 13 (Fig. 1c).…”
Section: Functional Characterization Of Szr4supporting
confidence: 76%
See 4 more Smart Citations
“…The alkalization was largely eliminated by the addition of a protonophore, 10 μM CCCP (carbonyl cyanide m-chlorophenylhydrazone), suggesting that SzR4 functions as an inward H + pump as reported previously 13 . The purified SzR4 showed a maximum absorption wavelength (λmax) at 557 nm, identical to that of SzR1 13 (Fig. 1c).…”
Section: Functional Characterization Of Szr4supporting
confidence: 76%
“…Asgard archaea are the closest prokaryotic species to ancestral eukaryotes 11 and have many genes unique to eukaryotes. Recently, a new microbial rhodopsin group, schizorhodopsin (SzR), was found in the assembled genomes of Asgard archaea and the metagenomic sequences of unknown microbial species 12,13 . A molecular phylogenetic analysis suggested that SzRs are located at an intermediate position between typical microbial rhodopsins, also called "type-1 rhodopsins" 14 , and HeR 5 , and thus they were named "schizo-(meaning "split" in Greek)" rhodopsin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations